Geosynonyms in the seventeenth-century Croatian dictionary: about some Italianisms - Ljubičić, Maslina (2008)
Ivan Belostenec's Latin-Croatian and Croatian-Latin two-volume dictionary, written in the 17th century, was edited more than sixty years after its author's death. Belostenec's lexicographic orientation is defined as tridialectal ; therefore his dictionary, consisting of kajkavian, chakavian and štokavian components, offers many geosynonyms. The diatopic variants of Dalmatia are present in the dictionary but not many of them are Italianisms.
Projekt MZOS
ENG